Teknik Inversi Pada Pemeriksaan Leukosit - MARGARETA HAITI; Lidwina Septie Christyawardani (LPPM STIKes Mitra Adiguna, 2023)
The preanalytic stage of the hematology laboratory examination is very important from patient preparation to specimen management. Homogeneization with inversion technique is one of the specimen management which also determines the valid result of a blood test. This study aims to determine the difference between primary, secondary and non-homogenized inversion inversion on leukocyte profile examination. The results of the statistical test showed that there was a significant difference, so every hematological examination had to be done an accurate homogenization according to the standard. Keywords: homogenization, inversion technique, leukocytes